Now you see it : how the brain science of attention will transform schools and business for the 21st century - Davidson, Cathy N., 1949- (New York : Viking, 2011)
Documents a 2003 experiment at Duke University where the author had free iPods issued to the freshman class to see how the device could be used academically, in a report that reveals other technological ideas that are revolutionizing education.
Introduction: I'll count: you take care of the gorilla -- Pt. 1. Distraction and difference: the keys to attention and the changing brain. Learning from the distraction experts -- Learning ourselves -- Pt. 2. The kids are all right. Project classroom makeover -- How we measure -- The epic win -- Pt. 3. Work in the future. The changing workplace -- The changing worker -- Pt. 4. The brain you change yourself. You, too, can program your VCR (and probably should) -- Conclusion: Now you see it -- Appendix. Twenty-first-century literacies: a checklist.
Includes bibliographical references and index.
Keywords: Attention; Distraction (Psychology); Neurosciences; Attention; Neurosciences; Personality; Psychology, Social